Penulisan dan Pembacaan Cerita Maulid Nabi di Kalangan Penganut Tarekat Syattariyah di Padang - Pramono Pramono (Jurnal Elektronik WACANA ETNIK, 2010)
This article is focused on discussing efforts to intreprate the manuscript “Kitab Fadilatu al-Syuhur: Menerangkan Sejarah Maulidnya Nabi Muhammad Shalallahu ‘Alaihi Wassalam Sampai Hijrah ke Negeri Madinah”  (KFSMSMNM) work of Imam Maulana Abdul Manaf Amin al-Khatib (d. 2006). The article is aimed to: 1) to make description of biography and creative process of Imam Maulana Abdul Manaf Amin al-Khatib; 2) to explain the text of manuscript KFSMSMNM; and 3) to explain phenomenon of literacy and strong verbal iterary tradition. The manuscript KFSMSMNM is not read by oneself but being read aloud to oneself. Thus, one understands the content of a manuscript KFSMSMNM because someone else reads it for them. This phenomenon is associated with Minangkabau people’s nature of literacy and strong verbal literary tradition, especially the adherents of Tarighat Syattariyah in Padang.